Induced male-sterility alters dry matter distribution in solanum villosum mill. - Ojiewo, C.O.; Murakam, K.; Masuda, M.; Agong', Stephen G. (ISHS, 2008)
African nightshades are leafy vegetables popular in Africa and South-East Asia for their high nutritional and medicinal value. The plants are strongly autogamic, exhibiting early and excessive flowering coupled with prolific fruit- and seed-set, which competes with the leaves for assimilates, resulting in extremely low leaf yields. The potential for suppressing or delaying this reproductive function through induced male-sterility, thereby improving and stabilizing leaf yields, was evaluated. Seeds of Solanum villosum were subjected to various doses of 60Co gamma-ray and 12C5+ ion irradiation. Pollen staining and anther structure studies at M2 progeny revealed four types of abnormalities compared with the wild type (W-T): acetocarmine-stained nonviable pollen, which stained black with potassium iodide solution (T-1); defective aborted pollen not stainable with acetocarmine (T-2); defective pollenless anthers (T-3); and extremely low pollen-producing type (T-4). In addition, a novel temperature-sensitive mutant with abnormal floral organs (T-5) was isolated from one line irradiated with 12C5+ ion beam. The T-5 produced 9.6% (143.7 g/plant) and 22.7% (147.4 g/plant) more biomass than the W-T in 2005 (131.2 g/plant) and 2006 (120.2 g/plant), respectively. Furthermore, the T-5 allocated 27.3 and 31.31% while the W-T allocated 19.2 and 19.5% of the total plant matter to leaves in 2005 and 2006, respectively. Conversely, while the T-5 allocated only 2.81 and 0.93%, the W-T allocated 40 and 33.81% of the total plant biomass to fruits in 2005 and 2006, respectively. These results can be attributed to elimination of the suppressing effects of fruits and seeds on vegetative growth. Male-sterility and the accompanying change in reproductive: vegetative balance is clearly a useful tool for circumventing source-sink imbalances that reduce leaf yields after anthesis in African nightshades.
Keywords: Solanum villosum; male-sterile; temperature-sensitive; dry matter; source-sink